The Psychosocial Correlates of Non-suicidal Self-Injury Within a Sample of Adolescents With Mood Disorder - Meng, Linlin; Qu, Diyang; Bu, He; Huo, Lijuan; Qi, Ling; Yang, Jiezhi; Zheng, Tiansheng; Du, Xiangdong; He, Kongliang; Wang, Yanni; Zhou, Yongjie (Frontiers in Public Health, 2022)
Background: According to the integrated theoretical model, adolescents’ behaviors were the outcome of the complex interplay between multiple levels. Non-suicidal self-injury (NSSI) is a serious and high prevalent problem among adolescents with mood disorders. However, a systematic perspective on psychosocial correlates among Chinese clinical adolescents is still rare. Method: The impact of several factors at the individual (i.e., sex, age, self-esteem, psychological distress), family (i.e., family structure, family income, family support), and social level (i.e., living environment, peer support, teacher support) on the frequency of NSSI behaviors were investigated in the current study. This research included 621 Chinese adolescents with mood disorders from 20 hospitals. Results: Three-steps hierarchical regression analyses indicated that lower levels of psychological distress and higher levels of self-esteem were most associated with less frequency of NSSI behaviors. In addition, family support was negatively associated with the frequency of NSSI behaviors. After controlling the factors at individual and family levels, no significant association was found between the factors at the social level and the frequency of NSSI behaviors. Conclusion: These findings provide preliminary support for the notion that adolescent self-esteem and family support may effectively shield them from problematic behavior; nevertheless, adolescents suffering from more emotional pain can be even riskier. Thus, further intervention strategies should consider the non-independence of individual capacities, co-combinatory effects of mood disorder, and family environment in treating those vulnerable Chinese adolescents.